Concerns in Reshaping Media Regulatory Environment - Dr. Poarkodi.N, Dr. N.C. Krishnapriya (South Eastern European Journal of Public Health, 2025)
Evolution of media and communication policies and regulations are an important area of inquiry in policy research. There have been several shifts in policies and regulations with globalisation and emergence of new digital technologies. In this background, the paper outlines the key areas of state intervention in media, including nationalisation, liberalisation and privatisation of media. The paper attempts to identify the milestones in the development of communication policies and regulatory measures, including telecommunications. Further, the paper will track the internationalisation of policies, facilitated by convergent digital technologies in the communication sector.